Parton distributions and LHC data - Rojo, J (2012)
In this contribution we briefly report on the progress and open prob- lems in parton distribution functions (PDFs), with emphasis on their implications for LHC phenomenology. Then we study the impact of the recent ATLAS and CMS W lepton asymmetry data on the NNPDF2.1 parton distributions. We show that these data provide the first constrains on PDFs from LHC measurements. Copyright © 2013 SIF.